When anger meets joy: how emotions mobilise and sustain the anti-coal seam gas movement in regional Australia. (2nd November 2018) - Ransan-Cooper, Hedda; A. Ercan, Selen; Duus, Sonya
ABSTRACT: In many countries, the expansion of unconventional gas exploration and development has been met with grassroots resistance; the scale and depth of which has surprised even movement organisers. An often-remarked feature of the movement's success is the teaming up of farmers and environmental organisers, historically at odds with one another on other environmental issues. This paper explores the role of emotions in building alliances, and mobilising opponents of coal seam gas (CSG) in a particular rural setting in Australia. Drawing on interviews with anti-CSG movement participants, the paper argues that emotions help to explain how the movement has mobilised and sustained alliances despite differences between movement participants. We find that while anger plays a central role in mobilising various anti-CSG actors, it is the combination of anger with joy which helps to sustain the anti-CSG movement in regional Australia. Our analysis reveals three key sites (individuals, within groups, and the public arena) where these emotions are expressed and negotiated, and emphasises the influence of the rural context in this process.